A rare case of lung squamous cell carcinoma coexisting with pulmonary MALT lymphoma presenting as a progressive pGGN. Issue 7 (7th September 2020) - Yang, Li; Wang, Ting; Ge, Mingjian; Zhang, Min; Cao, Youde; Guo, Shuliang
Abstract: Pulmonary extranodal marginal zone lymphoma of the mucosa‐associated lymphoid tissue (MALT) presenting as a progressive pure ground‐glass nodule (GGN) coexisting with lung squamous cell carcinoma has not been reported. A 65‐year‐old male presented with a progressive lung GGN in the left upper lobe identified six and a half years ago but showed no symptoms. The patient had a history of tuberculosis, squamous cell carcinoma, and stomach MALT lymphoma. The patient was diagnosed with lung squamous cell carcinoma coexisting with pulmonary MALT lymphoma through computed tomography (CT)‐guided lung biopsy. A progressive lung GGN presenting in a patient with squamous cell carcinoma does not always indicate multiple primary lung adenocarcinoma, especially when given a specific medical history. The development of MALT lymphoma in the lung presenting as GGNs suggests a possible association between these two entities. Abstract : Here, we present an extremely rare case of coexistence of lung squamous cell carcinoma with mucosa‐associated lymphoid tissue (MALT) lymphoma presenting as progressive lung ground‐glass nodules.